Enhancement of field electron emission properties of carbon nanotubes zinc oxide nanocomposites using single and multi step methods - Rika Noor Safitri (N/A, 2015)
Enhancement of field electron emission properties of carbon nanotubes zinc oxide nanocomposites using single and multi step methods by Rika Noor Safitri